Spletne skupnosti - Atanasova, Sara (Družboslovne razprave, 2014)
The social complexity and dynamics of online communities do not allow for them to be unambiguously defined which is why the concept attracts plural definitions and conceptualisations. The purpose of this paper is not to generate the most valid definition of the concept but to form a typology of online communities. Based on a synthesis of key definitions of the concept of online community and a critical evaluation of existing typologies, the paper proposes a new typology of online communities and presents their fundamental characteristics. The presented typology is based on three variables: (1) the prevailing relationship orientation of the online community; (2) the multi-functionality of the online community; and (3) types of online communities. The typology identifies 12 ideal types of online communities which can serve as a heuristic tool for further analyses, research, theorisations and the accumulation of new knowledge about such communities.
Keywords: Svetovni splet; World Wide Web; Community; Skupnost; Tipologija; Typology; spletne skupnosti